Seven new genera and thirty-four new species of buccinoid gastropods (Neogastropoda: Buccinidae) from the Aleutian Islands, Alaska - Mclean, James H.; Clark, Roger N. (Zootaxa, 2023)
Seven new genera and thirty-four new species of gastropods in the in the family Buccinidae, are described from the Aleutian Islands. The new taxa represent five subfamilies: Parancistrolepidinae Habe, 1972: Boreancistrolepis excelsus n. gen. & n. sp. Beringiinae Golikov & Starabogatov, 1975: Aleutijapelion mirandus n. gen. & n. sp.; Beringius nearensis n. sp., B. amliensis n. sp., B. bisulcatus n. sp., B. kiskensis n. sp., B. stanchfieldi n. sp., B. frausseni n. sp., B. aurulentus n. sp., B. maristempestus n. sp., B. undataformis n. sp.; Exiloberingius exiguus n. gen. & n. sp. Neptuneinae Stimpson, 1865: Aulacofusus canaliculatus n. sp., A. tanagaensis n. sp.; Neptunea aleutica n. sp., N. baxteri n. sp., N. dominator n. sp., N. petrelensis n. sp., N. quhmax n. sp., N. vesteraalen n. sp.; N. harrisoni n. sp., N. jewetti n. sp., Laevisipho galaxaios n. gen & n. sp., L. kessleri n. sp.; Volutopsiinae: Volutopsius nanus n. sp., Volutopsius gracilis n. sp.; Crebrivolutopsius labidentatus n. gen. & n. sp. Buccininae Rafinesque, 1815: Aleutibuccinum n. gen.; Castaneobuccinum orri n. gen. & n. sp., C. lauthi, n. sp., C. clinopsis n. sp., C. pagodaformis n. sp.; Sulcosinus carinatus n. sp.; Buccinum lanatum n. sp.; and Buccinum katharinae n. gen. & n. sp. The new genera and species are distinguished by the morphological characters of the shells and radulae.